COVID-19 outcome is not affected by anti-CD20 or high-titer convalescent plasma in immunosuppressed patients - Mary J. Kasten; Brian D. Lahr; Anusha Parisapogu; Zachary A. Yetmar; John C. O’Horo; Robert Orenstein; Pablo Moreno Franco; Raymund R. Razonable; Paschalis Vergidis; Aditya S. Shah; Mark J. Enzler; David J. Inwards; et al. (Scientific Reports, 2023)
Abstract The role of severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) convalescent plasma in the treatment of Coronavirus Disease 2019 (COVID-19) in immunosuppressed individuals remains controversial. We describe the course of COVID-19 in patients who had received anti-CD20 therapy within the 3 years prior to infection. We compared outcomes between those treated with and those not treated with high titer SARS-CoV2 convalescent plasma. We identified 144 adults treated at Mayo clinic sites who had received anti-CD20 therapies within a median of 5.9 months prior to the COVID-19 index date. About one-third (34.7%) were hospitalized within 14 days and nearly half (47.9%) within 90 days. COVID-19 directed therapy included anti-spike monoclonal antibodies (n = 30, 20.8%), and, among those hospitalized within 14 days (n = 50), remdesivir (n = 45, 90.0%), glucocorticoids (n = 36, 72.0%) and convalescent plasma (n = 24, 48.0%). The duration from receipt of last dose of anti-CD20 therapy did not correlate with outcomes. The overall 90-day mortality rate was 14.7%. Administration of convalescent plasma within 14 days of the COVID-19 diagnosis was not significantly associated with any study outcome. Further study of COVID-19 in CD20-depleted individuals is needed focusing on the early administration of new and potentially combination antiviral agents, associated or not with vaccine-boosted convalescent plasma.